Cationic Polymer Micelles as Carriers of Bioactive Sesquiterpene Lactones from Inula Helenium L. for Effective Treatment of Bacterial Biofilms - Rumena Stancheva; Tsvetozara Damyanova; Tsvetelina Paunova-Krasteva; Ralitsa Veleva; Tanya Topouzova-Hristova; Viktoria Ivanova; Antoaneta Trendafilova; Ivaylo Dimitrov; Stanislav Rangelov; Emi Haladjova (Pharmaceutics, 2025)
Objectives: Nanosized polymeric micelles (PMs) with an average size of about 80 nm and moderately positive ζ potential, based on an amphiphilic poly(4-methyl-piperazin-1-yl)-propenone)-b-polylactide (PMPP-PLA) block copolymer, were prepared. They were used as platforms for the delivery of bioactive sesquiterpene lactones from Inula helenium L. root extract. Methods: The PMs were characterized with good encapsulation efficiency as a maximum value of 72% was reached at a polymer-to-extract mass ratio of 10:1. The loaded micelles exhibited good colloidal stability. An in vitro release was performed showing a burst release profile. The biocompatibility of the resulting PMs was confirmed by assessing their cytotoxic effect on human keratinocytes in vitro by colorimetric assay and flow cytometry. Results: The systems demonstrated the capability to reduce the biomass of pre-formed Gram-positive and Gram-negative bacterial biofilms. Conclusions: The obtained data clearly determine a trend for a strong combined effect between the PMs and the root extract, distinguishing them with an excellent anti-biofilm potential and prospects for future applications in medical practice.